PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI UD. PINGUIN BANDAR LAMPUNG - Suryani Suryani (Business Perspective Journal, 2021)
This study aims to analyze and examine the effect of leadership style on the performance of UD. Pinguin Bandar lampung. The collection of data ‘re done through questionnaires and conducted on 45 employees of UD. Pinguin Bandar lampung. Analysis of the data in this study using SPSS version 18. This study does not use sampling techniques because the samples study entirely of the population which called the census data and testing techniques used in this study include the validity of the test, the Cronbach alpha reliability test, the classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis. The analysis showed that variable leadership style (X) = 0,001 <  = 0,05 shows the influence of variable leadership style on the performance of employees of UD. Pinguin Bandar Lampung (Y) is significant. Keywords: Leadership Style, Work Discipline, Motivation and Employee Performance